2018
DOI: 10.1016/j.cmet.2018.02.016
|View full text |Cite
|
Sign up to set email alerts
|

The Pericyte of the Pancreatic Islet Regulates Capillary Diameter and Local Blood Flow

Abstract: Efficient insulin secretion requires a well-functioning pancreatic islet microvasculature. The dense network of islet capillaries includes the islet pericyte, a cell that has barely been studied. Here we show that islet pericytes help control local blood flow by adjusting islet capillary diameter. Islet pericytes cover 40% of the microvasculature, are contractile, and are innervated by sympathetic axons. Sympathetic adrenergic input increases pericyte activity and reduces capillary diameter and local blood flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
194
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(205 citation statements)
references
References 82 publications
11
194
0
Order By: Relevance
“…It is also possible that not all pericytes have the capacity to respond to vasoactive agents. For instance only a subset of pericytes have been observed to express smooth muscle actin (αSMA) in the brain (Bandopadhyay et al, 2001), spinal cord (Roufail et al, 1995), retina (Nehls, 2004), and pancreatic islets (Almaça et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that not all pericytes have the capacity to respond to vasoactive agents. For instance only a subset of pericytes have been observed to express smooth muscle actin (αSMA) in the brain (Bandopadhyay et al, 2001), spinal cord (Roufail et al, 1995), retina (Nehls, 2004), and pancreatic islets (Almaça et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Blocking cholinergic receptors with atropine caused ischemia in pancreatic capillary beds 21 . Under increased glucose levels, during which parasympathetic activity increases, more rapid islet blood flow occurs relative to decreased glucose levels 22,24 . Conversely, stimulation of adrenergic nerve fibers decreases pancreatic blood flow 5,24 .…”
Section: Discussionmentioning
confidence: 99%
“…Under increased glucose levels, during which parasympathetic activity increases, more rapid islet blood flow occurs relative to decreased glucose levels 22,24 . Conversely, stimulation of adrenergic nerve fibers decreases pancreatic blood flow 5,24 . The increase in blood flow under parasympathetic activity may contribute to increased insulin release, although precise links between islet blood flow and hormone secretion remain to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Although it appears that pericytes are required for normal insulin secretion, it is still unknown whether pericytes directly communicate with beta cells or whether the majority of these changes are mediated by pericytes manipulating capillary blood flow to beta cells. A recent publication by Almaca et al demonstrated that pericytes can regulate capillary diameter and blood flow to islets in response to factors such as endothelin‐1 . The same study went on to show that an increase in beta cell activity resulted in a decrease in pericyte activity, manifesting as capillary dilation .…”
Section: Pericytes and Capillary Blood Flowmentioning
confidence: 97%